TV Religi Penjaga Aswaja: Sejarah dan Perkembangan TV9 – Nahdlatul Ulama Jatim - Vanny Sutria Jaya; Muhammad Khodafi (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2020)
Abstract: The research aims to determine the history and development of TV9 as a media for Nahdlatul Ulama. The focus contained in this article is: (1) What is the history of the founding of TV9. (2) What are the TV9 programs. (3) What is the purpose of making these programs. The approach used is the historical approach (diachronic perspective) and the descriptive-narrative approach, with the historical approach (diachronic perspective) the author aims to describe events that occurred in the past. While the descriptive-narrative approach is used to describe and analyze the development of TV9 programs and Aswaja values ​​in the TV9 program. In this case the researcher used the media dependency theory according to Sandra Ball Rokeach and Melvin Defleur. This research concludes that: (1) The establishment of TV9 was started from the concern and concern of three NU cadres namely, H Misbahul Munir, Hakim Jayli, Ahmad Taufik Arsyeb who felt a shared anxiety about the moral problems caused by television broadcasts. As well as the dream of making television for Islamic boarding schools and Nahdlatul Ulama. (2) TV9's programs have experienced rapid development, both quantitatively and qualitatively. (3) Almost all of TV9's programs aim to maintain, develop, spread, and preserve the values ​​of Aswajaanism. Keywords: History, developmetn, TV9